2014
DOI: 10.5489/cuaj.1774
|View full text |Cite
|
Sign up to set email alerts
|

Urethrocutaneous fistula post-Al-Ghorab shunt

Abstract: Priapism is a rare event that may be induced by clinical conditions and medications. Ischemic priapism (IP) is a compartment syndrome of the penis, and it constitutes a medical emergency that may cause significant morbidity on the erectile function in particular. We report a case of a 30-year-old male in his fourth episode of priapism. The aspiration and washing of the corpora cavernosa with saline solution were performed, followed by washing with adrenaline solution without resolution of the condition. Treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…The patients were treated with surgical debridement. Paladino et al (2014) reported necrosis and urethrocutaneous fistula due to Al-Ghorab procedure in a patient who was on valproic acid, clonazepam, haloperidol and levomepromazine for the treatment of schizophrenia. An inadvertent injury of the glandular urethra occurred during the Al-Ghorab procedure.…”
Section: Case Reportmentioning
confidence: 99%
“…The patients were treated with surgical debridement. Paladino et al (2014) reported necrosis and urethrocutaneous fistula due to Al-Ghorab procedure in a patient who was on valproic acid, clonazepam, haloperidol and levomepromazine for the treatment of schizophrenia. An inadvertent injury of the glandular urethra occurred during the Al-Ghorab procedure.…”
Section: Case Reportmentioning
confidence: 99%